Traditional Knowledge: Considerations for Protecting Water in Ontario - McGregor, Deborah (International Indigenous Policy Journal, 2012)
In Canada, the water crisis increasingly felt around the world is being experienced primarily in small, usually Indigenous, communities. At the heart of this issue lies an ongoing struggle to have Indigenous voices heard in the decision-making processes that affect their lives, lands, and waters. As part of ancient systems of Traditional Knowledge (TK), Indigenous people bear the knowledge and the responsibility to care for the waters upon which they depend for survival. A series of internationally developed documents has supported Indigenous peoples’ calls for increased recognition of the importance of TK in resolving environmental crises, including those involving water. Ontario provincial and Canadian federal governments have been developing legislative and regulatory documents to help fend off further water-related catastrophes within their jurisdictions. Despite such efforts, a number of barriers to the successful and appropriate involvement of TK in water management remain. Based on years of community-based and policy-related research with First Nations people involved in water-related undertakings, this article highlights progress made to date, and provides Indigenous viewpoints on what further steps need to be taken. Key among these steps are the need to restore and maintain Indigenous access to traditional territories and ways of life, and the requirement for mutually respectful collaboration between TK and Western science.